2018
DOI: 10.1016/j.anbehav.2017.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Social stability in semiferal ponies: networks show interannual stability alongside seasonal flexibility

Abstract: The version presented here may differ from the published version or from the version of the record. Please see the repository URL above for details on accessing the published version and note that access may require a subscription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
55
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 63 publications
2
55
0
Order By: Relevance
“…Using this metric of stability, we found that the manakin social networks were more stable than 76 expected by chance ( Fig. 1a), similar to other social animals (7,(28)(29)(30). However, stability was not constant, because each network fluctuated across a range of values (mean stability 0.43 ± SD 78 0.23; repeatability of stability 0, 95% CI 0-0.22).…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…Using this metric of stability, we found that the manakin social networks were more stable than 76 expected by chance ( Fig. 1a), similar to other social animals (7,(28)(29)(30). However, stability was not constant, because each network fluctuated across a range of values (mean stability 0.43 ± SD 78 0.23; repeatability of stability 0, 95% CI 0-0.22).…”
mentioning
confidence: 64%
“…Why are some social partnerships able to persist through time (7,18,29,30)? To understand how social structure might influence the fidelity of particular bonds over longer 124 timescales, we analyzed the annual persistence of 669 manakin partnerships from one season to the next ( Fig.…”
mentioning
confidence: 99%
“…Roosting associations in Bechstein's bats (Myotis bechsteinii) and Natterer's bats (Myotis nattereri) were found to remain stable across several years despite high fission-fusion dynamics (Kerth et al, 2011;Zeus et al, 2018). Stanley et al (2018) revealed that, despite seasonal fluctuations in gregariousness and overall weak social associations, semi-feral ponies (Equus caballus) maintained stable association preferences over three years. Finally, Firth and Sheldon (2016) showed that great tits' (Parus major) winter social associations carried over into their subsequent breeding season, as individuals bred nearer to those they were most associated with during winter.…”
Section: Introductionmentioning
confidence: 98%
“…Bands are typically stable, with few changes in group composition over time [18]. Mares will often remain in the same group for most (if not all) of their adult lives [19]-allowing for persistent social bonds between them [20]-and offspring remain with the group until 4-6 years of age [14,21]. Although the communicative repertoire of feral horses has been described as rudimentary [22], it has been shown to provide frequent and clear communication amongst group members [14,15,23,24].…”
Section: Introductionmentioning
confidence: 99%